The Effect of Cylindrical Grip Exercise on Increasing Upper Extremity Muscle Strength in Non-Hemorrhagic Stroke - Novita Kurnia Wulandari; Maria Wisnu Kanita; Mutiah Nur Khasanah (Prodi Keperawatan Purwokerto, Poltekkes Kemenkes Semarang, 2026)
Background: Non-hemorrhagic stroke is the most common type of stroke and can cause disability due to muscle weakness in the extremities, especially the upper extremities. One effort to prevent disability is to provide maintenance interventions in the form of physical exercises such as Range of Motion (ROM) and cylindrical grip exercises to increase muscle strength. Objective: This study aims to determine the effectiveness of cylindrical grip exercises on increasing upper extremity muscle strength in non-hemorrhagic stroke patients. Methods: This study used This study used a quantitative quasi-experimental design with a pre-test post-test with control design. The sample of this study was 44 respondents who were randomly divided into two groups. Results: The results of the Wilcoxon test analysis showed that the 22 respondents who received the functional cylindrical grip exercise intervention had an effect on increasing upper extremity muscle strength in nonhemorrhagic stroke patients with a p-value of 0.001, it shows 7 respondents (31.8%) experienced an increase in muscle strength, reaching a score of 4 and 5 in 3 respondents (13.6%). Conclusion: This study shows that functional cylindrical grip exercises for 10 minutes a day for 3 days have an effect on increasing upper extremity muscle strength in non-hemorrhagic stroke patients.